Teachers’ Practices in Developing Entrepreneurial Competence for Innovative Quality Education - Andrea Gracia-Zomeño; Eduardo García-Toledano; Ramón García-Perales; Ascensión Palomares-Ruiz (European Journal of Investigation in Health, Psychology and Education)
Entrepreneurial Competence (EC) is increasingly recognized as essential to foster innovation and enhance educational quality. This study explores how education professionals perceive and develop the EC within educational centres, using a qualitative approach through structured interviews with education professionals. The findings highlight the need for a more explicit and systematic development of the EC, emphasizing continuous teacher training in entrepreneurial approaches. While digital and paper-based resources support the EC, educators stress the importance of active and practical methodologies such as Project-Based Learning and Learning by Doing. Limited collaboration among educators is identified as a barrier to effectively foster EC. Moreover, the lack of strategic planning within educational institutions remains an obstacle. This study underscores the importance of introducing structured and innovative pedagogical approaches to ensure that students cultivate the skills necessary to navigate an evolving and uncertain future.